Community Approaches to Combat Dengue Transmission in Morelia, Michoacan - Sandoval, Ezequiel; Guzmán, Damaris; Muñiz, Bruno Michel (International Journal of Medical Students, 2025)
BACKGROUND: Around the world, it has been shown that many countries know a diversity of community strategies techniques approaches to combat Dengue Transmission. Due to a lack of awareness and use of dengue prevention measures, there is no indication of people in Mexico experiencing a decline in the virus's ability to spread. METHODS: Data were collected through surveys conducted on Google Forms, where participants were asked about their personal physical, chemical, and household protection measures. The study sample and population selection are ‘non-probabilistic or targeted. It included people aged 18 years and older who live in the Primo Tapia Poniente neighborhood of Morelia, Michoacán, Mexico. Exclusion criteria were applied, such as the death of the patient, refusal to give informed consent, no longer willing to participate, lack of communication or, moving. RESULTS: Prevalence of the use of household protection tools Comparing knowledge with usage in Table 1 shows that 69% use three or more tools, and 20% use two. According to the surveys, 69% of the people knew at least one household protection tool against dengue and accepted the fumigation service. In comparison, 30% of the people knew at least one household protection tool against dengue but did not accept the fumigation service. Prevalence of actions or use of personal protection tools From the whole sample, 28% use two or more personal protection tools, followed by mosquito repellent (17%), but 55% do not use it. 30% of participants do not use any personal protection tools. CONCLUSION: Increasing dengue prevention and having a population more equipped to manage the dengue season is crucial, as this research has shown that the community uses more informed preventive measures.